AGC Including ELD and Emission Coordination Using Sine Cosine Algorithm - Ahmed Oday Oleiwi; Ahmed Jasim Sultan (Journal of Techniques)
The aim of conventional AGC is to regulate the demand load of the area with taking into account the sharing power with the others area and also the frequency deviation and tie-line power deviation within minimum error steady-state.  The proposed coordination's goal is to regulate the demand load between the interconnected area when taking into account the optimal dispatch and emission effect. The two-area that be consist of three units in each one (hydro, thermal, and gas) is used of proposed system. The optimization algorithms were used to find the best operating point of the system by tuning the integral gain are located in ACE that named primary control and Generation allocation logic named secondary controller. The Particle Swarm Optimization (PSO) and Sine Cosine Algorithm (SCA) are used to tune gains of the integral (I) controller to show the superiority in identifying robust controller. The simulation results prove that the SCA with proposed coordination is very effectiveness as compared with PSO algorithm in enhance the dynamic performance and reduce overshoot, maximum frequency deviation, and net tie line power flow deviation error for a given load change and disturbed the demand load between two-area as economic.